PENGARUH METODE PEMBELAJARAN INDEX CARD MATCH TERHADAP HASIL BELAJAR SISWA SD - Silvi Ayu Novikasari; Anggra Lita Sandra Dewi; Endang Wahju Andjariani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
Education is an obligation that must be taken from an early age, not as a necessity and in the end educational activities become a routine. One of the learning methods in education that has interesting results for researchers is the Index Card Match method. Learning outcomes are the results achieved by students in an effort to master learning at school. It is hoped that with the Index Card Match method students can easily understand the learning material for theme 6, sub-theme 1 more clearly and make students active in learning so that student learning outcomes continue to increase. This research was conducted on fourth grade students of SD Negeri 01 Rowokangkung Lumajang. By involving 19 students of class IVA as the control class and 20 students of class IVB as the experimental class. In this study, calculations using SPSS obtained results in the control class (no treatment) with a total pretest value of 0.085 > 0.05. while the posttest value was obtained with a total of 0.033 <0.05. In the experimental class (after treatment) the pretest results were obtained with a total of 0.002 <0.05 while the posttest values ​​obtained a value of 0.017 <0.05. Based on the calculation results above, it is known that a significance value or Asymp.Sig.(2-tailed) of 0.000 <0.05 or Ha is accepted. This means that there are significant differences in the learning outcomes of the experimental and control classes, or the learning method with the Index Card Match in the thematic subjects, theme 6, sub-theme 1, which has a significant effect on student learning outcomes.